2018
DOI: 10.1016/j.ymthe.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Global Transcriptional Response to CRISPR/Cas9-AAV6-Based Genome Editing in CD34+ Hematopoietic Stem and Progenitor Cells

Abstract: Genome-editing technologies are currently being translated to the clinic. However, cellular effects of the editing machinery have yet to be fully elucidated. Here, we performed global microarray-based gene expression measurements on human CD34 hematopoietic stem and progenitor cells that underwent editing. We probed effects of the entire editing process as well as each component individually, including electroporation, Cas9 (mRNA or protein) with chemically modified sgRNA, and AAV6 transduction. We identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
105
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(112 citation statements)
references
References 58 publications
0
105
1
Order By: Relevance
“…As a proxy to cellular response to the delivery of exogenous RNA, we considered recently published transcriptional responses of a human cell type to delivery of non-viral RNA sequences encoding cas9 protein and CRISPR gRNA to hemoglobin B locus (HBB), 4 hereafter referred to as 'cas9 mRNA' (3). Specifically, the delivery of cas9 mRNA into hematopoietic stem and progenitor cells (HSPCs) was found to induce a strong antiviral transcriptional response (3).…”
Section: Relationship Between Transcriptional Responses To Exogenousmentioning
confidence: 99%
See 2 more Smart Citations
“…As a proxy to cellular response to the delivery of exogenous RNA, we considered recently published transcriptional responses of a human cell type to delivery of non-viral RNA sequences encoding cas9 protein and CRISPR gRNA to hemoglobin B locus (HBB), 4 hereafter referred to as 'cas9 mRNA' (3). Specifically, the delivery of cas9 mRNA into hematopoietic stem and progenitor cells (HSPCs) was found to induce a strong antiviral transcriptional response (3).…”
Section: Relationship Between Transcriptional Responses To Exogenousmentioning
confidence: 99%
“…As a proxy to cellular response to the delivery of exogenous RNA, we considered recently published transcriptional responses of a human cell type to delivery of non-viral RNA sequences encoding cas9 protein and CRISPR gRNA to hemoglobin B locus (HBB), 4 hereafter referred to as 'cas9 mRNA' (3). Specifically, the delivery of cas9 mRNA into hematopoietic stem and progenitor cells (HSPCs) was found to induce a strong antiviral transcriptional response (3). Several genes involved in innate antiviral response such as interferon stimulatory genes (ISGs), interferon regulatory factors (IRF1, IRF7, IRF9) and the cytosolic foreign RNA sensor RIG-1 were upregulated by cas9 mRNA delivery (3).…”
Section: Relationship Between Transcriptional Responses To Exogenousmentioning
confidence: 99%
See 1 more Smart Citation
“… Cromer et al [1] recently reported global transcriptional changes occuring in cells in response to CRISPR/Cas9 gene editing. Using a CD34 + hematopoietic and progenitor stem cell model, they observed differentially expressed genes enriched for immune, stress and apoptotic processes following treatment with a CRISPR/Cas9-AAV6 genome-editing system.…”
mentioning
confidence: 99%
“…The sgRNA in each case was designed to target the hemoglobin B ( HBB ) locus which is a clinically relevant model for sickle cell disease (in the scope of several translational research programs leveraging CRISPR/Cas9 technology). All experiments in Cromer et al [1] were performed in CD34 + hematopoietic stem cells obtained from four individual donors to account for potential individual variability to genome editing machinery [4]. The query signature lists were restricted to genes belonging to 10,174 best inferred genes (BING) in the L1000 assay.…”
mentioning
confidence: 99%